2001
DOI: 10.1161/hy1101.096115
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Nitric Oxide Availability in Normotensive and Hypertensive Rats With Failing Hearts After Myocardial Infarction

Abstract: Abstract-Endothelial NO synthase, being deficient in arginine and/or tetrahydrobiopterin, produces in addition to NO a significant concentration of superoxide (O 2 Ϫ ). We investigated whether such an imbalance between O 2 Ϫ and NO production is present in dysfunctional aortas of Wistar-Kyoto rats (WKY) and spontaneously hypertensive rats (SHR) with failing hearts after myocardial infarction. Heart failure was induced by permanent occlusion of the left coronary artery, resulting in a large infarction of the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 52 publications
4
37
0
Order By: Relevance
“…In addition, increased free radical production by the failing heart might be expected to oxidize tetrahydrobiopterin to result in uncoupling of NOS to produce O 2 Ϫ ⅐ rather than NO (35). The present data demonstrating O 2 Ϫ ⅐ effects on resistance vessel function in the setting of CHF are similar to previous studies using isolated aortic ring preparations that demonstrated impaired conduit vessel endothelial function in CHF animals that was associated with increased O 2 Ϫ ⅐ and ONOO Ϫ production (35,42). In those studies, treatment with SOD improved endothelium-dependent vasodilation and normalized cGMP responses to the NO donor sodium nitroprusside, indicating that endothelial dysfunction resulted from inactivation of NO by O 2 Ϫ ⅐ (3).…”
Section: Endothelial Dysfunction and Vascular Osupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, increased free radical production by the failing heart might be expected to oxidize tetrahydrobiopterin to result in uncoupling of NOS to produce O 2 Ϫ ⅐ rather than NO (35). The present data demonstrating O 2 Ϫ ⅐ effects on resistance vessel function in the setting of CHF are similar to previous studies using isolated aortic ring preparations that demonstrated impaired conduit vessel endothelial function in CHF animals that was associated with increased O 2 Ϫ ⅐ and ONOO Ϫ production (35,42). In those studies, treatment with SOD improved endothelium-dependent vasodilation and normalized cGMP responses to the NO donor sodium nitroprusside, indicating that endothelial dysfunction resulted from inactivation of NO by O 2 Ϫ ⅐ (3).…”
Section: Endothelial Dysfunction and Vascular Osupporting
confidence: 85%
“…Several investigators have reported that superoxide (O 2 Ϫ ⅐) production is increased both in myocardial mitochondria (19) and in coronary arteries (3,4,42) …”
mentioning
confidence: 99%
“…47 In the present study, we demonstrate that the VSMC and aorta from SHRs exhibit decreased levels of NO which may be because of the decreased expression of eNOS as well as to the enhanced levels of O 2 − . In this regard, the decreased expression of eNOS and NO has been reported in cardiac myocyte and vascular smooth muscle of hypertensive animals 35,48,49 and suggests that the increased BP in SHRs may also be attributed to the decreased levels of NO. Furthermore, eNOS knockout mice were shown to exhibit increased BP.…”
Section: Discussionmentioning
confidence: 85%
“…Coronary and peripheral endothelial bioavailability of NO is severely reduced after experimental MI [11][12][13] and in patients with heart failure. 14 -17 In addition to the impairment of endothelium-dependent vasodilation, several mechanisms have now been identified whereby reduced eNO bioavailability may contribute to the pathophysiology of heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…10 Interestingly, there is evidence that reduced eNO availability may play an important role in the pathophysiology of heart failure both after experimental MI [11][12][13] and in patients with heart failure. 14 -17 Inhibition of eNO production results in impaired endothelium-dependent vasodilation, reduced myocardial neovascularization, 18 and impaired vascular endothelial growth factor-induced mobilization of endothelial progenitor cells (EPCs).…”
mentioning
confidence: 99%